The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s00421-014-2922-x
|View full text |Cite
|
Sign up to set email alerts
|

Irisin and FNDC5: effects of 12-week strength training, and relations to muscle phenotype and body mass composition in untrained women

Abstract: This file was dowloaded from the institutional repository Brage NIH -brage.bibsys.no/nih Ellefsen, S., Vikmoen, O., Slettaløkken, G., Whist, J. E., Nygård, H., Hollan, I.... Rønnestad, B. (2014). Irisin and FNDC5: effects of 12-week strength training, and relations to muscle phenotype and body mass composition in untrained women. MethodsEighteen untrained women performed 12 weeks of progressive whole body heavy strength training, with measurement of strength, body composition, expression of irisin-related gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
4
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 48 publications
4
58
4
2
Order By: Relevance
“…3). These findings are consistent in part with the previous reports that exercise could increase the production of irisin from FNDC5 (Ellefsen et al 2014;Liu et al 2015;Nygaard et al 2015). However, the FNDC5 protein levels were significantly decreased after 2-h recovery, despite the increase in its mRNA levels.…”
Section: Discussionsupporting
confidence: 83%
“…3). These findings are consistent in part with the previous reports that exercise could increase the production of irisin from FNDC5 (Ellefsen et al 2014;Liu et al 2015;Nygaard et al 2015). However, the FNDC5 protein levels were significantly decreased after 2-h recovery, despite the increase in its mRNA levels.…”
Section: Discussionsupporting
confidence: 83%
“…In the present study, the correlation between irisin and TSH levels was not significant. In line, Stengel et al [34] and Ellefsen et al [35] reported lack of associations between levels of irisin, TSH and/or thyroid hormones in euthyroid individuals. However, Ruchala et al [27] observed a negative correlation between irisin and TSH.…”
Section: Resultsmentioning
confidence: 83%
“…27 While these intriguing data suggested a role for irisin in response to exercise training in both mice and humans, results from several follow up studies came to varying conclusions. 27,33,[43][44][45][46][47][48] These studies have all addressed the questions of whether exercise training increases circulating irisin concentrations and some of the investigations determined if exercise-induced increases in irisin cause a beiging of scWAT in humans. A combined endurance and strengthtraining program in male subjects had no effect on circulating irisin concentrations, 33 although interestingly, and as discussed above, these training programs only resulted in modest, if any increase in beiging of scWAT.…”
Section: Irisinmentioning
confidence: 99%
“…45 In contrast, strength training for 12 wks in women ages 20-32 y that resulted in increased lean body mass and improved strength did not result in changes in circulating irisin concentration. 43 In another study, young, healthy women preformed vibration exercise, a moderate intensity exercise that resembles shivering. While a single bout of vibration exercise resulted in a statistically significant~2-fold increase in circulating irisin, there was no effect of 6 wks of vibration exercise on serum irisin concentrations.…”
Section: Irisinmentioning
confidence: 99%